2023
DOI: 10.1186/s12915-023-01525-1
|View full text |Cite
|
Sign up to set email alerts
|

Folylpolyglutamate synthetase mRNA G-quadruplexes regulate its cell protrusion localization and enhance a cancer cell invasive phenotype upon folate repletion

Abstract: Background Folates are crucial for the biosynthesis of nucleotides and amino acids, essential for cell proliferation and development. Folate deficiency induces DNA damage, developmental defects, and tumorigenicity. The obligatory enzyme folylpolyglutamate synthetase (FPGS) mediates intracellular folate retention via cytosolic and mitochondrial folate polyglutamylation. Our previous paper demonstrated the association of the cytosolic FPGS (cFPGS) with the cytoskeleton and various cell protrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…C1 was found serendipitously, and we anticipate that its structure may serve as a template for the development of improved non-classical antifolates that have optimal properties for selective inhibition of FPGS-deficient, methotrexate-resistant cells, and address the clinical need for intervention strategies with decreased risk of relapse. Recent studies revealed that a subpopulation of FPGS protein may associate with the cytoskeleton and motor proteins, allowing cells to channel folates to cellular subcompartments, depending on folate availability (Stark et al, 2021(Stark et al, , 2023. This indicates that the function of FPGS extends beyond simply mediating intracellular accumulation of folates or classical antifolates, and additional research is required to test the effects of cytoskeleton-associated FPGS on sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…C1 was found serendipitously, and we anticipate that its structure may serve as a template for the development of improved non-classical antifolates that have optimal properties for selective inhibition of FPGS-deficient, methotrexate-resistant cells, and address the clinical need for intervention strategies with decreased risk of relapse. Recent studies revealed that a subpopulation of FPGS protein may associate with the cytoskeleton and motor proteins, allowing cells to channel folates to cellular subcompartments, depending on folate availability (Stark et al, 2021(Stark et al, , 2023. This indicates that the function of FPGS extends beyond simply mediating intracellular accumulation of folates or classical antifolates, and additional research is required to test the effects of cytoskeleton-associated FPGS on sensitivity to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%